Pregnancy Outcome of Single Previous cesarean Section - Jha, M (Journal of Nepal Health Research Council, 2009)
Background: The main aim of this study is to determine the maternal and fetal outcome of pregnancy among women with one previous caesarean section at term in relation to vaginal delivery, post partum complication, neonatal complication like low Apgar score, fetal weight and admission in special baby unit. Methods: This is a prospective and descriptive study done in a sample size of 100. Inclusion criteria were term pregnancy, single live fetus with cephalic presentation with one previous caesarean section. During study period total number of obstetric admissions was 3546 and 115 cases were admitted with previous one caesarean section. Result: Out of 100 cases, 31 cases had vaginal delivery and 69 cases had caesarean section. Among 31 vaginal deliveries, 24 cases had spontaneous vaginal delivery and 7 had assisted delivery with vacuum, main indication of vacuum delivery was to cut short the second stage of labor that was in 5(71.43%) cases. Among 69 caesarean section cases, 51 had emergency caesarean section and 18 had elective caesarean section and cephalopelvic disproportion was the main indication in both the groups. Most common complication was scar dehiscence and postpartum hemorrhage. There were two still births in each group and one minute APGAR score was slightly better in caesarean section. Conclusions: Patients with previous caesarean section are at high risk of repeat emergency or elective caesarean section. About one in three patients with previous caesarean section delivered vaginally. In the present study postpartum hemorrhage was the commonest complication, which was found in caesarean section, and only one puerperal pyrexia was seen in case of vaginal delivery. Key words: Cephalopelvic disproportion, Premature rupture of membrane, Septicemia, Vacuum delivery DOI: 10.3126/jnhrc.v7i1.2275 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 25-28